Identification of P2X(4) receptor transmembrane residues contributing to channel gating and interaction with ivermectin - Jelínkova, Irena; Vávra, Vojtech; Jindrichova, Marie; Obsil, Tomas; Zemkova, Hana W; Zemkova, Hana; Stojilkovic, Stanko S (Pflugers Archiv, 2008)
Ivermectin (IVM), a large macrocyclic lactone, specifically enhances P2X(4) receptor-channel function by interacting with residues of transmembrane (TM) helices in the open conformation state. In this paper, we used cysteine-scanning mutagenesis of rat P2X(4)-TMs to identify and map residues of potential importance for channel gating and interaction with IVM. The receptor function was unchanged by mutations in 29 different residues, and among them, the IVM effects were altered in Gln(36), Leu(40), Val(43), Val(47), Trp(50), Asn(338), Gly(342), Leu(346), Ala(349), and Ile(356) mutants. The substitution-sensitive Arg(33) and Cys(353) mutants could also be considered as IVM-sensitive hits. The pattern of these 12 residues was consistent with helical topology of both TMs, with every third or fourth amino acid affected by substitution. These predominantly hydrophobic-nonpolar residues are also present in the IVM-sensitive Schistosoma mansoni P2X subunit. They lie on the same side of their helices and could face lipids in the open conformation state and provide the binding pocket for IVM. In contrast, the IVM-independent hits Met(31), Tyr(42), Gly(45), Val(49), Gly(340), Leu(343), Ala(344), Gly(347), Thr(350), Asp(354), and Val(357) map on the opposite side of their helices, probably facing the pore of receptor or protein and playing important roles in gating.
Keywords: Animals; Protein Conformation; ivermektin; Rats; buněčné linie; mutace; Molecular Sequence Data; Amino Acid Sequence; Humans; Ivermectin; gating iontového kanálu; metoda terčíkového zámku; Receptors, Purinergic P2X4; purinergní receptory P2X4; Cell Line; sekvence aminokyselin; Models, Molecular; lidé; antiparazitární látky; Receptors, Purinergic P2; zvířata; Patch-Clamp Techniques; Antiparasitic Agents; Ion Channel Gating; molekulární modely; Mutation; konformace proteinů; krysa rodu Rattus; molekulární sekvence - údaje; purinergní receptory P2